The Influence of Perceived Ease of Use on the Intention to Use Mobile Payment: Attitude toward Using as Mediator - Setiawan, Maggie; Setyawati, Christina Yanita (Accounting Department, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jawa Timur, 2020)
The purpose of this research is to find out the influence of perceived ease of use, perceived ease of use, and attitude toward using on the intention to use mobile payment and the influence of perceived ease of use on the intention to use mobile payment through attitude toward using as mediation variable for traders at Taman Puspa Raya (TPR) market. Taman Puspa Raya Market (TPR) is used as an object in this research because there is a shift of payment system to the traders at the TPR market that causes the traders to have similarities in using fintech as payment system alternative. This research uses a quantitative method. The population in this research is 168 traders at the TPR market that using mobile payment as a payment alternative. The number of samples in this research is 45 respondents, and the response rate in is 100%. In this research, data analysis is done by Structural Equation Modeling Partial Least Square (SEM-PLS). The results of this research prove that all hypotheses are accepted. These results indicate another support evidence for the theory of acceptance model (TAM). A suggestion to future researchers is to get closer to the traders before the study is made so that traders will be more proactive and willing to help in the process of filling out the questionnaire so that the data obtained is not biased. Suggestion for traders is traders can be more careful and double-check existing transactions by ensuring that the transaction is successful and there is a notification on the merchant's cellphone.